Thermal microscopy of electronic materials. (1st March 2016) - Heiderhoff, Ralf; Makris, Andreas; Riedl, Thomas
Abstract: Due to an increasing level of device integration and progressive device miniaturization, the thermal management requires comprehensive microscopic investigations of thermal properties as heat dissipation on the micro- and nanoscale. Today heat management is one of the key limiting factors in a wide range of electronic applications, e.g. in automotive and electro-mobility. In this review, an overview on far-field and near-field thermal microscopy techniques using infrared thermography, laser beam techniques, and scanning probe microscopy is given. The common aim of all these approaches is to get access to temperature distributions, heat transport mechanisms, thermos-elastic quantities, as well as thermoelectric properties of electronic materials on microscopic levels. Examples for devices inspections, for integrated circuit analysis, and for thin film technology applications at micro and nanoscale are presented.